2017
DOI: 10.1002/14651858.cd004610.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment for Clostridium difficile -associated diarrhoea in adults

Abstract: No firm conclusions can be drawn regarding the efficacy of antibiotic treatment in severe CDI as most studies excluded patients with severe disease. The lack of any 'no treatment' control studies does not allow for any conclusions regarding the need for antibiotic treatment in patients with mild CDI beyond withdrawal of the initiating antibiotic. Nonetheless, moderate quality evidence suggests that vancomycin is superior to metronidazole and fidaxomicin is superior to vancomycin. The differences in effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(139 citation statements)
references
References 84 publications
3
125
0
11
Order By: Relevance
“…Metronidazole remains cost effective and readily available. In systematic reviews, there appears to be no difference between metronidazole and vancomycin therapy for initial episodes of CDI . There are concerns regarding possible generation of vancomycin‐resistant enterococci with vancomycin use.…”
Section: What Antibiotics Should Be Used For Treatment Of An Initial mentioning
confidence: 99%
“…Metronidazole remains cost effective and readily available. In systematic reviews, there appears to be no difference between metronidazole and vancomycin therapy for initial episodes of CDI . There are concerns regarding possible generation of vancomycin‐resistant enterococci with vancomycin use.…”
Section: What Antibiotics Should Be Used For Treatment Of An Initial mentioning
confidence: 99%
“…Evidence from systematic reviews and meta-analyses suggests that fidaxomicin is better than vancomycin at reducing recurrence 22232425262728293031. Fidaxomicin might therefore be a better treatment option than vancomycin, except for patients with severe infections.…”
Section: What Are the Latest Recommendations For Management?mentioning
confidence: 99%
“…One review found that sustained symptomatic cure was improved with teicoplanin compared with vancomycin;39 however, the quality of evidence is low, and the drug is not available in the US.…”
Section: What Other Treatments Are On the Horizon?mentioning
confidence: 99%
“…6 The treatment of AAD or CD associated diarhea include non-pharmacologic, pharmacologic including antibiotics (metronidazole, vancomycine, fidaxomicin), probiotics and surgery. 3,[7][8][9][10][11][12] The aims of this study is to know the incidence of AAD, Clostridium difficile infection and other gastrointestinal symptoms in hospitalized adult patients.…”
Section: Introductionmentioning
confidence: 99%